PENGARUH TAHAPAN KEPUTUSAN PEMBELIAN TERHADAP KEPUASAN PELANGGAN PADA TOKO TERHUBUNG (ONLINE) - , JULIA ADRIANA, Dr. Sahid Susilo Nugroho, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the influence of factors such as the quality of the information, web site design, merchandise attributes, transaction capability, response time, security / privacy, payment, delivery, and customer service in influencing overall customer satisfaction of online shopping. This study conduct a quantitative approach with survey using purposive sampling method, which obtained 254 respondents who have been doing electronic online shopping. Based on the results of the regression test performed, this study findings that among the nine variables that can affect customer satisfaction in online shopping, only merchandise attributes, delivery, and customer service that can significantly affect customer satisfaction. While the information quality, web site design, transaction capability, response time, security / privacy, and the payment failed to be a significant predictor of customer satisfaction. This result is in contrast to a previous study conducted by Liu et al., 208 in China. This is due to differences in the selection of objects and setting research. Given this research is expected to provide input for online shopping in the making strategies in order to improve customer satisfaction in online shopping.